2019
DOI: 10.3389/fvets.2019.00048
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fiber and Intestinal Health of Monogastric Animals

Abstract: Animal performance, feed efficiency, and overall health are heavily dependent on gut health. Changes in animal production systems and feed regulations away from the use of antibiotic growth promoters (AGP) have necessitated the identification of strategies to optimize gut health in novel and effective ways. Among alternatives to AGP, the inclusion of dietary fibers (DF) in monogastric diets has been attempted with some success. Alternative feedstuffs and coproducts are typically rich in fiber and can be used i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
194
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 249 publications
(207 citation statements)
references
References 102 publications
7
194
0
6
Order By: Relevance
“…Inulin and chicory root exhibited fast and intense fermentation patterns with the highest cumulative gas productions (A) and rate of fermentation (R MAX ) and the lowest time to half asymptote (B) and time to reach R MAX (T MAX ). Chicory root, with a higher ratio of soluble to insoluble polysaccharides and the soluble fraction being mainly composed of fructans, is highly fermentable and therefore is more likely to be fermented at the end of the small intestine (55) . Chicory pulp displayed slower fermentation kinetics which is related to its high insoluble fibre content (high NDF and ADF levels) and its low amount in fructans, mainly composed of polysaccharides with high polymerisation degree (30) .…”
Section: Discussionmentioning
confidence: 99%
“…Inulin and chicory root exhibited fast and intense fermentation patterns with the highest cumulative gas productions (A) and rate of fermentation (R MAX ) and the lowest time to half asymptote (B) and time to reach R MAX (T MAX ). Chicory root, with a higher ratio of soluble to insoluble polysaccharides and the soluble fraction being mainly composed of fructans, is highly fermentable and therefore is more likely to be fermented at the end of the small intestine (55) . Chicory pulp displayed slower fermentation kinetics which is related to its high insoluble fibre content (high NDF and ADF levels) and its low amount in fructans, mainly composed of polysaccharides with high polymerisation degree (30) .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, seaweed polysaccharides are atypical in structure to terrestrial glycans, and were found to resist gastric acidity, host digestive enzymes, and GI absorption [347]. Maternal seaweed extract supplementation can reduce both sow fecal Enterobacteriaceae populations at parturition and piglet E. coli populations at weaning [348]. Also, seaweeds are good source of prebiotics that improve intestinal microbiota and may exert positive effects on IBD and IBS [349,350].…”
Section: Alimentary Disordersmentioning
confidence: 99%
“…The situation has necessitated finding alternatives to AGP for healthy animal production. Different alternatives to AGP, including oligosaccharides and polysaccharides as prebiotics, have been evaluated with some success ( Jha et al., 2019a ; Yadav and Jha, 2019 ). These options are sought to maintain or improve the gut health of animals, as is essential for optimum growth, better feed efficiency, and overall health.…”
Section: Introductionmentioning
confidence: 99%
“…These options are sought to maintain or improve the gut health of animals, as is essential for optimum growth, better feed efficiency, and overall health. Emerging evidence indicates that there is a close relationship between intestinal microbiota and nutrition utilization ( Jha et al., 2019a ), which in turn affect the overall performance and health of animals ( Jha and Berrocoso, 2016 ). Intestinal microbiota can be manipulated by nutrition programming in poultry, during both the prehatch and posthatch period of life ( Jha et al., 2019b ).…”
Section: Introductionmentioning
confidence: 99%